Manifesto for the future of work and organizational psychology. Issue 3 (4th May 2019) - Bal, P. Matthijs; Dóci, Edina; Lub, Xander; Van Rossenberg, Yvonne G. T.; Nijs, Sanne; Achnak, Safâa; Briner, Rob B.; Brookes, Andy; Chudzikowski, Katharina; De Cooman, Rein; De Gieter, Sara; De Jong, Jeroen; et al.
ABSTRACT: This manifesto presents 10 recommendations for a sustainable future for the field of Work and Organizational Psychology. The manifesto is the result of an emerging movement around the Future of WOP (seewww.futureofwop.com ), which aims to bring together WOP-scholars committed to actively contribute to building a better future for our field. Our recommendations are intended to support both individuals and collectives to become actively engaged in co-creating the future of WOP together with us. Therefore, this manifesto is open and never "finished." It should continuously evolve, based on an ongoing debate around our professional values and behavior. This manifesto is meant, first of all, for ourselves as an academic community. Furthermore, it is also important for managers, decision makers, and other stakeholders and interested parties, such as students, governments and organizations, as we envision what the future of WOP could look like, and it is only through our collective efforts that we will be able to realize a sustainable future for all of us.